From Fragmented Routes to Integrated Governance: Balancing Affordability and Operator Viability in Bogor’s Urban Public Transport - Suharto (Journal of Intelligent Decision Making and Information Science, 2026)
Urban public transport in rapidly growing cities of the Global South faces a persistent tension between passenger affordability and operator financial viability. This paper addresses this challenge through a mixed-methods study conducted in Bogor, Indonesia, where fragmented route networks, individually owned fleets, and aging vehicles have produced unreliable services and uncertain revenues. We adopt a sequential explanatory design that integrates quantitative transport modeling with qualitative institutional analysis. The quantitative phase examines travel patterns, vehicle operating costs, passengers’ ability to pay (ATP), and willingness to pay (WTP) through household and on-board surveys, origin-destination matrices, and PTV VISUM simulations. The qualitative phase draws on semi-structured interviews with transport officials, operators, and users to explore regulatory and governance constraints. Our results reveal a structural imbalance: the vehicle-operating-cost-based fare for conventional minibuses is IDR 5,094 per passenger trip, while average ATP is IDR 4,072 and average WTP is IDR 3,742. This gap indicates that passengers possess greater financial capacity than their stated willingness to pay, suggesting perceived service utility remains insufficient. Furthermore, aggregate seven-year fare revenue covers only 4.3% of estimated long-term operating and fleet-replacement costs. Fleet rationalization analysis shows that an optimized network would require an 80.4% reduction in vehicles, improving the cost-recovery ratio from 0.043 to 0.219. However, even under optimized conditions, fare revenue covers only 21.9% of costs. We therefore propose an integrated four-pillar framework combining demand-based route planning, professional operator management, performance-based financing with transparent subsidies, and enforceable regulatory policies. The study’s primary contribution lies in demonstrating that technical optimization alone cannot resolve the affordability-viability dilemma without corresponding governance reform and sustained fiscal commitment. These findings offer actionable insights for policymakers in Bogor and comparable emerging cities worldwide.